Christian Spirituality As The Foundation For Implementing “Poda Nalima” In The Toba Caldera Region In Indonesia (Journal of Namibian Studies : History Politics Culture, 2023)
This research is motivated by the degradation of the Poda Nalima philosophy. This study aims to investigate the implementation of Poda Nalima in the Toba Caldera region. The research method used was field research conducted in the Toba Caldera area. The results of this study indicate that Poda Nalima has been implemented through counseling in places of worship, installing billboards, formal district-level meetings, the TARHILALA program, the procurement of trash bins, government and community mutual assistance, and a cleanliness campaign by the Family Welfare Empowerment in Indonesia, namely Pemberdayaan Kesejahteraan Keluarga (PKK) group. Christian spirituality is the foundation for implementing Poda Nalima in the Toba Caldera region.